Brief communication: CESM2 climate forcing (1950-2014) yields realistic Greenland ice sheet surface mass balance - Noël, Brice (author); Van Kampenhout, Leonardus (author); Jan Van De Berg, Willem (author); Lenaerts, Jan T.M. (author); Wouters, B. (author); R. Van Den Broeke, Michiel (author) (The Cryosphere, 2020)
We present a reconstruction of historical (1950–2014) surface mass balance (SMB) of the Greenland ice sheet (GrIS) using a high-resolution regional climate model (RACMO2; ∼ 11 km) to dynamically downscale the climate of the Community Earth System Model version 2 (CESM2; ∼ 111 km). After further statistical downscaling to 1 km spatial resolution, evaluation using in situ SMB measurements and remotely sensed GrIS mass change shows good agreement. Comparison with an ensemble of previously conducted RACMO2 simulations forced by climate reanalysis demonstrates that the current product realistically represents the long-term average and variability of individual SMB components and captures the recent increase in meltwater runoff that accelerated GrIS mass loss. This means that, for the first time, climate forcing from an Earth system model (CESM2), which assimilates no observations, can be used without additional corrections to reconstruct the historical GrIS SMB and its recent decline that initiated mass loss in the 1990s. This paves the way for attribution studies of future GrIS mass loss projections and contribution to sea level rise. Physical and Space Geodesy